Fertilizer replacement value of organic fertilizers: Implications for locally relevant and tailored fertilizer recommendations - Gebrehana, Getachew Zerihun; Mesfin, Tewodros; Ebrahim, Mohammed; Abera, Wuletawu; Tamene, Lulseged D.; Chernet, Meklit (2024)
The application of Fertilizer Replacement Value (FRV) as a key metric for quantifying the nutrient content of various organic matters, organic fertilizers, and other Integrated Soil Fertility Management (ISFM) practices significantly enhances the efficacy of hyper-localization analysis in Decision Support Tool (DST) advisories. This method is exceptionally valuable for formulating precise, site-specific macronutrient recommendations tailored to diverse cropping systems and agro-ecologies. It achieves this by providing a reliable assessment of the nutrient contributions from a range of organic materials, whose nutrient content can differ widely. Consequently, FRV offers a robust quantitative framework for evaluating various ISFM practices and their influence on soil fertility, culminating in recommendations that are both insightful and impactful. Integrating FRV into DST advisories, through a comprehensive understanding of the FRV of organic inputs, empowers farmers to make more strategic decisions about investments in inorganic fertilizers. This can lead to a reduced reliance on costly synthetic fertilizers, while ensuring that the recommendations are relevant and practical for the local farming conditions, thereby increasing the likelihood of adoption by farmers.